Green Governance and Carbon Emission Transparency: Does Firm Age Matter? - Baroroh, Niswah; Harto, Puji (Accounting Analysis Journal, 2025)
Purpose: This research aims to examine the influence of an independent board of commissioners, green strategy, and green investment on Carbon Emission Disclosure (CED), and to analyze the role of firm age as a moderating variable among the relationships. Method: The research uses a quantitative approach with object is non-financial companies listed on the IDX from 2021 to 2024 with total of 800, sampling using purposive sampling with a total of 204 observations units. This research was analyzed using Moderated Regression Analysis (MRA) with E-views tools. Findings: The results show that independent boards of commissioners and green investments significantly and positively influence CED. Meanwhile, the green strategy does not have a significant impact. Also, firm age can strengthen the influence of independent boards of commissioners and green investments on CED but not on the influence of green strategy. Novelty: These findings provide theoretical contributions in enriching the literature related to carbon disclosure in developing countries by combining the perspectives of Stakeholder Theory, Legitimacy Theory, and Resource-Based View. Originally, this research offered the latest empirical evidence on the role of organizational characteristics in moderating the effectiveness of sustainability strategies on carbon emission reporting.